2004
DOI: 10.1007/s10616-005-0703-4
|View full text |Cite
|
Sign up to set email alerts
|

Production of a self-activating CBM-factor X fusion protein in a stable transformed Sf9 insect cell line using high cell density perfusion culture

Abstract: Factor Xa is a serine protease, whose high selectivity can be used to cleave protein tags from recombinant proteins. A fusion protein comprised of a self-activating form of factor X linked to a cellulose-binding module, saCBMFX, was produced in a stable transformed Sf9 insect cell line. The activity of the insect cell produced saCBMFX was higher than the equivalent mammalian cell produced material. A 1.5 l batch fermentation reached a maximum cell concentration of 1.6 Â 10 7 cells ml À1 and a final saCBMFX con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 31 publications
1
11
0
Order By: Relevance
“…A detailed review of the acoustic settler has been published by Shirgaonkar et al (2004). 6 cells/mL and 40 Â 10 6 cells/mL have been reported using the acoustic settler (Zhang et al 1998;Gorenflo et al 2004) and Gorenflo obtained 10 Â 10 6 CHO cells/mL in 100 L scale (Gorenflo et al 2002). An improvement of the technology was brought by installing an air-driven system able to suck the cell broth into the settler chamber and to back flush the cells into the bioreactor, avoiding the use of a peristaltic pump and enabling to empty the chamber completely (Gorenflo et al 2003).…”
Section: Acoustic Settlermentioning
confidence: 99%
“…A detailed review of the acoustic settler has been published by Shirgaonkar et al (2004). 6 cells/mL and 40 Â 10 6 cells/mL have been reported using the acoustic settler (Zhang et al 1998;Gorenflo et al 2004) and Gorenflo obtained 10 Â 10 6 CHO cells/mL in 100 L scale (Gorenflo et al 2002). An improvement of the technology was brought by installing an air-driven system able to suck the cell broth into the settler chamber and to back flush the cells into the bioreactor, avoiding the use of a peristaltic pump and enabling to empty the chamber completely (Gorenflo et al 2003).…”
Section: Acoustic Settlermentioning
confidence: 99%
“…Perfusion culture has been frequently studied and often involves the use of pumps to recirculate the cells. Pump damage was found to reduce the viability of a variety of animal cell types, including insect (Merten, 2000;Gorenflo et al, 2004), hybridoma (LaPorte et al, 1996) and CHO cells (Kim et al, 2008). Yet, in perfusion culture, the rate of pumping is far lower than here, circulation rates being about 1 to 10 bioreactor volumes/day (Merten, 2000;Kim et al, 2008) compared to ~ 100 to ~ 200 per day here.…”
Section: An Overall Perspective From Both Studiesmentioning
confidence: 99%
“…In the case of stably transformed insect cells, baculovirus infection is no longer necessary for expression of the recombinant protein. The hypothesis is that in the cases of stably transformed insect cells the potential of the high cell density culture methods such as fed batch and perfusion (Gorenflo et al, 2004) can be fully realized. High cell density culture methods which can result in significant increases in cell densities increase the potential for bioprocess intensification (Griffiths, 1990) resulting in a subsequent increase in the volumetric productivity without increasing the size of the reactor, and a concurrent decrease in the requirements for liquid handling and overall downstream unit operations (Chisti and Moo-Young, 1996;Smith et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…Earlier workers have described perfusion culture methods for recombinant protein expression using Sf-9-BEVS (Jäger, 1996;Zhang et al, 1998); the system however, is better suited for cells which express a secreted protein in a stable continuous manner, allowing the product to be harvested for prolonged periods of time. Gorenflo et al (2004) studied the expression of a recombinant protein saCBMFX in stably transformed Sf-9 insect cells in the perfusion system and reported that the protein produced had a higher activity than that expressed in a mammalian expression system. Stably transformed Drosophila S2 cells have also been used for the expression of several human proteins including erythropoietin, interleukin-2 (hIL-2), and human transferrin (hTF).…”
Section: Introductionmentioning
confidence: 99%